Corrosion protection studies of stainless steel alloy in hydrochloric acid by using electropolymerized poly (N-imidazolyl tetrahydrophthalamic acid) - I.Ali, Mayasa; A.Saleh, Khulood (International Journal of Engineering and Technology, 2018)
The present work reports the electrochemical synthesis of poly (N-imidazolyl tetra hydro phthalamic acid) (PIP) from monomer (N-imidazolyl tetra hydro phthalamic acid) (NIP) in aqueous solution on surface of stainless steel (working electrode) by using electrochemical polymerization technique. The corrosion protection test for coated and uncoated stainless steel (SS) by polymer was studied in 0.2 M HCl solution by followed Tafel and Potentiostatic procedures. The structure of PIP was characterized by Fourier Transform Infrared (FTIR) spectroscopy and Atomic Force Microscope (AFM). Parameters of corrosion that include corrosion current density (icorr), corrosion potential (Ecorr) and protection efficiency (PE %) were studied. The effect of temperature in the range (293-323) K on the protection efficiency of coated and uncoated stainless steel also was studied. Polymer was modified by adding nanomaterials (Zinc Oxide (normal) (ZnOn) and reduced graphene oxide (rGO)) into monomer solution to improve protection effeciency. The results obtained shown higher protection efficiency at 293 K. Kinetic and thermodynamic of activation parameters were studied for corrosion process for coated and uncoated stainless steel in acidic medium.Â